Benefits Trafficking: human trafficking of older adults and adults with disabilities - Thomas, Anna; Strickland, Heather (Frontiers in Rehabilitation Sciences, 2024)
An emerging type of trafficking is targeting overlooked at-risk adults3. Benefits Trafficking1 is the systematic recruitment, harboring, neglect, and financial exploitation4 of elder and disabled adults who receive government benefits such as Social Security, Veteran's Benefits, Medicaid, and Medicare. Traffickers often pose as kind-hearted individuals offering to provide care for atrisk adults3 in an in-home setting. Once recruited, at-risk adults3 are stripped of their government benefits, held against their will, moved from location to location, and denied basic needs such as food, clothing, and adequate shelter. While Benefits Trafficking1 is a basic civil rights violation issue, it is also a growing public health issue. Victims of Benefits Trafficking1 are often the forgotten at-risk adults3 who have fallen through the cracks of various mental health systems, are unhoused, and no longer have a social support system in place. This area of human trafficking is unresearched and its prevalence is largely unknown outside of the few entities working in this space. This paper focuses mainly on raising awareness of Benefits Trafficking1 and suggestions for future funding and research initiatives.